Developing Industry-Relevant Soft Skills Through Peer-Engaged Project Approach (PePA): A Vocational Education Perspective - Prasetya, Tri Adi; Munadi, Sudji; Sukardi, Thomas; Setiyawan , Andri (Journal of Applied Engineering and Technological Science (JAETS), 2025)
The development of soft skills remains a critical challenge in vocational education, as the curriculum often prioritises technical competencies while neglecting systematic integration of interpersonal skills. This study aims to develop and evaluate the Peer-Engaged Project Application Model (PePA), a project-based learning framework designed to enhance communication, teamwork, and problem-solving through structured peer engagement. Employing a Research and Development (R&D) approach based on the ADDIE model, the research was conducted in the D4 Mechanical Engineering Program at Yogyakarta State University. The PePA model was tested on a group of 15 students in the Fabrication Construction Practices course. Data were collected through Likert-scale questionnaires, structured observations, and semi-structured interviews, and analysed using descriptive and inferential statistics, along with qualitative techniques. The implementation of PePA resulted in improved performance in soft skills, with average scores increasing from 3.03 to 3.65 (communication), 3.20 to 3.78 (teamwork), and 3.13 to 3.70 (problem-solving). The model was also rated as “very valid” by expert evaluators, with an average validation score ranging from 3.58 to 3.85. These findings suggest that PePA is a feasible and effective learning model for strengthening vocational students' soft skills in alignment with industry expectations. The model has potential applicability beyond engineering education and supports policy recommendations for integrating soft skills into vocational curricula.